Development and Evaluation of a Rural Longitudinal Neonatal Resuscitation Program Telesimulation Program (MOOSE: Maine Ongoing Outreach Simulation Education) - Melendi, Misty; Zanno, Allison E.; Holmes, Jeffrey A.; Chipman, Micheline; Cutler, Anya; Stoddard, Henry; Seften, Leah M.; Gilbert, Anna; Ottolini, Mary; Craig, Alexa; Mallory, Leah A. (American Journal of Perinatology, 2024)
Neonatal resuscitation is a high-acuity, low-occurrence event and many rural pediatricians report feeling underprepared for these events. We piloted a longitudinal telesimulation (TS) program with a rural hospital's interprofessional delivery room teams aimed at improving adherence to Neonatal Resuscitation Program (NRP) guidelines and teamwork.A TS study was conducted monthly in one rural hospital over a 10-month period from November 2020 to August 2021. TS sessions were remotely viewed and debriefed by experts, a neonatologist and a simulation educator. Sessions were video recorded and assessed using a scoring tool with validity evidence for NRP adherence. Teamwork was assessed using both TeamSTEPPS 2.0 Team Performance Observation Tool and Mayo High-Performance Teamwork Scale.We conducted 10 TS sessions in one rural hospital. There were 24 total participants, who rotated through monthly sessions, ensuring interdisciplinary team composition was reflective of realistic staffing. NRP adherence rate for full code scenarios improved from a baseline of 39 to 95%. Compared with baseline data for efficiency, multiple NRP skills improved (e.g., cardiac lead placement occurred 12× faster, 0:31 seconds vs. 6:21 minutes). Teamwork scores showed improvement in all domains.Our results demonstrate that a TS program aimed at improving NRP and team performance is possible to implement in a rural setting. Our pilot study showed a trend toward improved NRP adherence, increased skill efficiency, and higher-quality teamwork and communication in one rural hospital. Additional research is needed to analyze program efficacy on a larger scale and to understand the impact of training on patient outcomes.
Keywords: simulation; neonatal resuscitation; telesimulation; rural health; interprofessional team training; program development